Influence of intensity offree-stream turbulenceon heat transfer fromcircularcylinderin a channel - Исатаев, М.С.; Омаралина, А.; Есеналиева, А.; Молдабекова, Д.; Шалбаева, Ж. (Recent Contributions to Physics, 2016)
A study of local heat transfer coefficient is allowed to establish: first, the heterogeneity of effects cluttering the flow of the heat front and aft area of the vehicle and, secondly, the difference of heat transfer from the feed half in the presence of currents in the channel. To account for the influence of the clutter flow on heat transfer of a circular cylinder it is necessary to introduce three amendments on the average flow rate, taking into account the heterogeneity of heat transfer in the front and aft areas, as well as the nature of the flow in the Wake behind the body. In addition, obtained empirical formulae for the calculation of the average Nusselt number over the entire surface of the cylinder in the presence of periodic vortices and frustrations in their absence.Also obtained an empirical formula for the calculation of heat transfer near the critical point of the front cylinder. The study of heat transfer of a circular cylinder was conducted in the interval 0<q<0.9 and 2≤Re≤2·105, for 0.7≤Pr≤550 and 0.4≤ε≤4.8 %.